Analysis of Fiscal Policy and Financial Sustainability in Improving the Country's Economic Stability - Muslim, Muslim; Bata Ilyas, Muh. Fadhel G; Sani, Amar (Yayasan Vifada Cendikia Indonesia, 2024)
This study aims to comprehensively analyze the role of fiscal policy and financial sustainability in enhancing economic stability, particularly in developing nations facing budgetary constraints and economic uncertainty. The research seeks to identify key components of fiscal sustainability and highlight the importance of proactive fiscal planning, institutional reforms, and evidence-based strategies to foster resilience and mitigate economic vulnerabilities. This research adopts a qualitative systematic literature review (SLR) approach to synthesize findings from relevant empirical and theoretical studies published after 2018. The study develops a multidimensional framework for understanding the interaction between fiscal policies and financial sustainability by examining a broad range of scholarly articles, reports, and policy papers. The analysis focuses on key fiscal mechanisms, including countercyclical measures, automatic stabilizers, and governance frameworks. The findings reveal that fiscal discipline, efficient taxation, and responsible debt management are essential to financial sustainability. Proactive budgetary policies, such as automatic stabilizers and counter-cyclical spending, can help stabilize economies during crises. However, the study identifies significant challenges in developing nations, including limited fiscal capacity, weak institutional frameworks, and reliance on external debt. The research emphasizes the need for institutional reforms to strengthen fiscal transparency, enhance public financial management, and foster accountability to build public trust and investor confidence. This study contributes to fiscal policy literature by presenting a holistic framework integrating budgetary sustainability and economic resilience. The practical recommendations highlight the importance of equitable tax policies, strategic public spending, and institutional capacity-building to support sustainable economic growth and long-term financial stability. Future research is recommended to validate these findings further through empirical case studies across different economic contexts.